Uncertainty of facade sound insulation by a Round Robin Test. Evaluations of low-frequency procedure and single numbers. (15th August 2016) - Scrosati, Chiara; Scamoni, Fabio; Prato, Andrea; Secchi, Simone; Fausti, Patrizio; Astolfi, Arianna; Barbaresi, Luca; D'Alessandro, Francesco; Di Bella, Antonino; Schenone, Corrado; Zambon, Giovanni
Abstract: The international standard ISO 140-5 for the measurement of the sound insulation of building facades has been recently replaced by the new standard ISO 16283-3. The revised standard includes the procedure for measurements at low frequencies down to 50 Hz. The uncertainty of facade sound insulation, in particular at low frequencies, was evaluated by a Round Robin Test, conducted in a full-scale experimental building at the Construction Technologies Institute of the National Research Council of Italy (ITC-CNR). Each of the 10 teams involved in the RRT replicated the tests 5 times, for a total of 50 measurements. The different measurement positions inside the receiving room were compared. In particular, all the teams involved in the RRT followed the low-frequency procedure, assessing corner and center room positions; the energy average values according to ISO 16283-3 were considered and the relative uncertainty, in terms of repeatability and in situ reproducibility standard deviations, was compared with the ones measured and calculated following the default measurement procedure. It was found that the uncertainty of the low-frequency procedure is higher than that of the default procedure. This would suggest the need to investigate further the reliability of the low-frequency procedure. At high frequency, the significant uncertainty values found are probably caused by the loudspeakers directivity and position; this aspect need to be investigated in greater detail, as well. Highlights: Comparison between default and LF measurement procedure is made on the same façade. High uncertainty in LF range is found, in particular with LF measurement procedure. Proposal of an alternative LF measurement procedure with 4-corner set average. Actual need for and reliability of LF procedure in non-diffuse field is discussed.